Development of Predictive Index for Default Treatment At Multibacillary Leprosy in District Sampang - Rukua, Muhammad Syarif; Martini, Santi; Notobroto, Hari Basuki (Jurnal Berkala Epidemiologi, 2015)
ABSTRACTDefault relating to the regularity of treatment in the patients taking the drugs. If the leprosy patients taking medication irregularly, then the leprosy bacteria can become resistant or immune to Multy Drug Therapy, so the symptoms persist and even worsen. The purpose of this study was to determine the indicators and develop a predictive index formula default incidence of leprosy treatment. This type of research was a case control design. The sample size in this study was 62 respondents. The sampling technique in this study used simple random sampling technique. Data collection techniques done with interviews with the questionnaire. The results showed that a candidate indicator variables (p <0.25) is income (p value = 0.013), access to health care (p value = 0.022), the role of health workers (p value = 0.032), knowledge (p value = 0.001), and family support (p value = 0.023), perception of the disease (p value = 0.098), leprosy reactions (p value = 0.198). Variables as indicators of default treatment of leprosy patients are the role of health workers, family support, knowledge, and income. The predictive index of default treatment at multibacillary leprosy patients are (-1666+ 1451 * Revenues (low) + 1989 * Role of Health Personnel (less instrumental) + 1.338 * Knowledge (less) + 1543 * Support Family (unfavorable). This index has a 79% accuracy rate. This index is expected to be used as a measuring tool in helping health workers to screen patients with leprosy who are undergoing treatment, so early can know where the potential patients defaulting treatment.Keywords: indicators, predictive index, default of treatment, leprosy, multibacillary